2017
DOI: 10.17979/reipe.2017.0.13.2585
|View full text |Cite
|
Sign up to set email alerts
|

Los estereotipos de género y las TICs en estudiantes de secundaria

Abstract: ResumenEste trabajo explora las diferencias de género en estudiantes de secundaria a la hora de interactuar con las TICs. La investigación fue realizada con una muestra de 351 alumnos de centros educativos públicos de Galicia. Se aplicó un cuestionario en el que se medían aspectos relacionados con el acceso, experiencia, frecuencia y uso que hacían, tanto de los computadores como de internet. Se aplicaron escalas para evaluar la percepción de autoeficacia en el manejo de internet y de computadores, las actitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Yücel and Rızvanoğlu found that girls showed a lower perception of computer competence and a higher perception of code di culty compared to boys in middle school children [21]. It was also reported that there was a gender difference in favor of men regarding computer and internet access, frequency of use, and experience in young people [22]. Another study pointed out that while men feel competent in digital technologies, especially in technical and educational modules, women use these technologies more for social purposes(Grande-de-Prado).…”
Section: Discussionmentioning
confidence: 98%
“…Yücel and Rızvanoğlu found that girls showed a lower perception of computer competence and a higher perception of code di culty compared to boys in middle school children [21]. It was also reported that there was a gender difference in favor of men regarding computer and internet access, frequency of use, and experience in young people [22]. Another study pointed out that while men feel competent in digital technologies, especially in technical and educational modules, women use these technologies more for social purposes(Grande-de-Prado).…”
Section: Discussionmentioning
confidence: 98%
“…Estudios han profundizado en la materia, ya que, además, desde la educación se pueden frenar dichas visiones erráticas. Así es el caso de la reciente investigación llevada a cabo por (Castro Balsa & Trigo, 2017), donde se efectuó un estudio sobre el acceso, experiencia, frecuencia y uso que hacían, tanto de los ordenadores como de Internet los jóvenes en Galicia (España). Los resultados revelaron que hay claras diferencias de género en las actividades que tienden a hacer en Internet.…”
Section: Introductionunclassified
“…As [18] indicate, the problem of the digital gender gap is a phenomenon that continues to exist, women and men are on the Internet, but not in the same way, or with the same visibility, or with the same aims.Concern about students' perceptions of gender stereotypes towards Internet use is turned into studies. This is the case of the recent research carried out by [4], where a study was carried out on the access, experience, frequency and use made of both computers and the Internet by young people in Galicia (Spain). The results revealed that there are clear gender differences in the ABSTRACT The existence of gender stereotypes in relation to the use of the Internet led to the need to carry out the present study, which approaches young people perception of the use of the Internet and technologies.…”
mentioning
confidence: 99%